Negative electrode material, electrochemical device, and electronic apparatus
By adding amorphous carbon and carbon-based additives to the negative electrode material of sodium ion battery to form a three-dimensional electron-conducting and ion-conducting network, the problem of insufficient energy density and rate performance of existing sodium ion battery negative electrode materials is solved, and higher energy density and rate performance is achieved.
Patent Information
- Application Number
- CN202311416738.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-27
AI Technical Summary
The energy density of existing sodium ion battery anode materials is low and the rate performance is poor, mainly due to the low compaction density of hard carbon materials and the high risk of sodium analysis.
By adding amorphous carbon and carbon-based additives to the negative electrode material, the particle size distribution and the dimension of the carbon-based additives are controlled to form a uniform and stable three-dimensional electron-conducting and ion-conducting network, thereby improving the energy density and rate performance of the electrochemical device.
The energy density and rate performance of sodium ion batteries are significantly improved, achieving higher compaction density and better kinetic performance.
Smart Images

Figure BDA0004521495530000101 
Figure BDA0004521495530000111 
Figure BDA0004521495530000121
Abstract
Description
Technical Field
[0001] The invention relates to a negative electrode material, an electrochemical device and an electronic device. Background Art
[0002] Sodium-ion batteries have potential application value in two-wheeled vehicles, low-speed vehicles, energy storage, etc., due to their lower cost than lithium-ion batteries and higher energy density than lead-acid batteries. However, sodium-ion batteries are relatively less mature at present, and there is still much room for improvement in energy density, rate performance, etc.
[0003] At present, the negative electrode of commercial sodium-ion batteries mainly uses hard carbon materials, which have the advantages of high gram capacity, low cost, and good low-temperature performance. However, hard carbon materials have more pore structures and larger interlayer spacing, resulting in low compaction density. In addition, hard carbon mainly relies on pore filling when storing sodium at low voltage, which has a relatively large risk of sodium precipitation. As a result, when hard carbon is used as a negative electrode material for sodium-ion batteries, its energy density is low and its rate performance is poor. Therefore, how to improve the compaction density and kinetic properties of hard carbon materials to improve their energy density and rate performance has become one of the key tasks in the current development of hard carbon negative electrodes. Summary of the invention
[0004] In order to solve the defects of low energy density and poor rate performance of negative electrode materials used in sodium ion batteries in the prior art, the present invention provides a negative electrode material, an electrochemical device and an electronic device. The electrochemical device containing the negative electrode material of the present invention has high energy density and excellent rate performance.
[0005] In a first aspect, the present invention provides a negative electrode material, comprising amorphous carbon and a carbon-based additive; wherein the amorphous carbon comprises hard carbon, and the dimensional matching degree between the amorphous carbon and the carbon-based additive is W, and W satisfies: 3.5≤W≤4.5; wherein W is calculated according to the following formula: W=2(d90-d10) / d50+D;
[0006] Wherein, d10, d50 and d90 represent the particle size of the amorphous carbon;
[0007] D represents the dimension of the carbon-based additive, and D is 0, 1, 2 or 3.
[0008] In a second aspect, the present invention provides an electrochemical device, comprising a negative electrode sheet, wherein the negative electrode sheet comprises a current collector layer and a negative electrode material layer located on the current collector layer, wherein the negative electrode material layer comprises the negative electrode material as described above.
[0009] In a third aspect, the present invention provides an electronic device comprising the electrochemical device as described above.
[0010] The positive and progressive effects of the present invention are:
[0011] The present invention provides a negative electrode material with a specific dimensional matching degree W. By controlling the particle size distribution of amorphous carbon and the dimension of a carbon-based additive in the negative electrode material, the carbon-based additive forms a uniform and stable three-dimensional electron-conducting and ion-conducting network on the surface of the amorphous carbon and between particles; further, by adjusting the ratio of the average particle size d50' of the carbon-based additive and the d50 of the amorphous carbon, the energy density and rate performance of the electrochemical device are significantly improved. DETAILED DESCRIPTION
[0012] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0013] Anode Materials
[0014] In the negative electrode material of the first aspect of the present invention: the negative electrode material comprises amorphous carbon and a carbon-based additive; wherein the amorphous carbon comprises hard carbon, and the dimensional matching degree between the amorphous carbon and the carbon-based additive is W, and W satisfies: 3.5≤W≤4.5; wherein W is calculated according to the following formula: W=2(d90-d10) / d50+D;
[0015] Wherein, d10, d50 and d90 represent the particle size of the amorphous carbon;
[0016] D represents the dimension of the carbon-based additive, and D is 0, 1, 2 or 3.
[0017] In the present invention, the maximum particle size of the amorphous carbon particles with a volume fraction of 10% from small to large is recorded as d10, the maximum particle size with a volume fraction of 50% from small to large is recorded as d50, and the maximum particle size with a volume fraction of 90% from small to large is recorded as d90. The d10, d50 and d90 of the amorphous carbon refer to the d10, d50 and d90 of the amorphous as a whole. The d10, d50 and d90 of the amorphous carbon are measured by the following method: 50 mg of the sample is added with 5 drops of 1% ethylphenyl polyethylene glycol aqueous solution, and then 20 mL of deionized water is added to ultrasonically disperse it fully, and the particle size volume distribution is tested using a laser particle size analyzer. The particle refractive index is 2.68, the solvent refractive index is 1.33, and the shading degree is 5%-10%.
[0018] In the present invention, the d50' of the carbon-based additive is measured by the following method: the carbon-based additive particles are placed under a transmission electron microscope for observation, more than 100 particles in an arbitrary area are selected, the size of each particle in the longest direction is counted, and the average value is calculated to obtain the average diameter, which is d50' (the particles counted are single particles, and agglomerated particles need to be counted as monomers).
[0019] The difference between d90 and d10 (d90-d10) can be used to evaluate the difference in particle size distribution of most amorphous carbon (mainly hard carbon) particles, and (d90-d10) / d50 can be used to evaluate the particle size distribution width of most amorphous carbon particles. When the particle size distribution width is different, the stacking mode, porosity and pore size of amorphous carbon particles in the pole piece will also be different.
[0020] Those skilled in the art generally understand that amorphous carbon includes hard carbon and / or soft carbon. The amorphous carbon described in the present invention at least includes hard carbon. Optionally, the weight percentage of hard carbon in the amorphous carbon is more than 90%, and the weight percentage refers to the weight percentage of hard carbon in the whole amorphous carbon.
[0021] In the present invention, the amount of the carbon-based additive can be 0.1%-12%.
[0022] In an optional embodiment of the present invention, the amount of the carbon-based additive is 0.1%-12%, more preferably 0.1%-10%, for example 0.5%, 1.0% or 2.0%, where the percentage is the weight percentage of the carbon-based additive to the amorphous carbon.
[0023] In some optional embodiments, the negative electrode material further satisfies: 0.001≤d50' / d50≤0.12, preferably satisfies 0.001≤d50' / d50≤0.1, wherein d50' represents the average particle size of the carbon-based additive.
[0024] The carbon-based additive of the present invention has two main functions. One is to fill the pores between the amorphous carbon particles to increase the compaction density of the pole piece, thereby improving the energy density of the battery (sodium ion battery); the other is to connect the amorphous carbon particles to improve the conductivity of the pole piece, thereby improving the rate performance of the electrochemical device, such as the sodium ion battery. Selecting a carbon-based additive that matches the amorphous carbon particles helps to simultaneously improve the energy density and rate performance of the electrochemical device. The inventors believe that when (d90-d10) / d50 is relatively small, the particle size distribution of amorphous carbon particles is narrow, a large number of large pores exist in the amorphous carbon particles during the stacking process, and most of the amorphous carbon particles are in point contact with each other, and the compaction density and conductivity are poor. By filling the pores with high-dimensional carbon-based additives and further selecting large-scale particles of carbon-based additives for coordination, the energy density and rate performance can be improved; when (d90-d10) / d50 is relatively large, the particle size distribution of amorphous carbon particles is wide, and small particles of amorphous carbon particles will fill the pores between large particles during the stacking process. There will be a large number of small pores in the gaps. Low-dimensional carbon-based additives can fill the pores more efficiently, and further by selecting small-scale carbon-based additive particles for coordination, the energy density and rate performance can be improved; when (d90-d10) / d50 is moderate, the particle size distribution of amorphous carbon particles is moderate, and the amorphous carbon particles have moderate pores during the stacking process. At this time, if a carbon-based additive with too high a dimension or too large a size is used, the pores cannot be filled. If a carbon-based additive with too low a dimension or too small a size is used, the electron transmission distance will increase. Therefore, carbon-based additives with appropriate dimensions and particle sizes need to be matched.
[0025] When the negative electrode material satisfies 3.5≤2(d90-d10) / d50+D≤4.5 and 0.001≤d50' / d50≤0.1, the dimensions and particle size of the carbon-based additive match those of the amorphous carbon particles, which can obtain the optimal packing density and conductive network, and help to obtain the optimal energy density and rate performance of the electrochemical device.
[0026] Those skilled in the art are aware that carbon-based additives can be divided into 0-dimensional, 1-dimensional, 2-dimensional and 3-dimensional according to the degree to which their spatial dimension (D) is constrained by the nanoscale.
[0027] When the dimension D of the carbon-based additive is 0, the carbon-based additive may be selected from one or more of conductive carbon black, carbon quantum dots and fullerenes.
[0028] When the dimension D of the carbon-based additive is 1, the carbon-based additive may be selected from one or more of carbon nanotubes, carbon fibers and carbon nanowires.
[0029] When the dimension D of the carbon-based additive is 2, the carbon-based additive may include thin-layer graphene, wherein the thin-layer graphene is graphene with 5 or less layers.
[0030] When the dimension D of the carbon-based additive is 3, the carbon-based additive may be selected from one or more of artificial graphite, natural graphite, multilayer graphene and mesophase carbon microspheres, wherein the multilayer graphene is graphene with 5 or more layers.
[0031] It should be noted that in the present invention, according to actual needs, carbon-based additives of more than two dimensions can be used together with amorphous carbon. When the carbon-based additive is a mixture of carbon-based additives of more than two dimensions, D takes the dimension of the carbon-based additive with the highest weight percentage. For example, the carbon-based additive is a mixture of carbon-based additives of two dimensions, and D takes the dimension of the carbon-based additive with a weight percentage of more than 50%. That is to say, in the first aspect of the present invention, when D=0, it does not necessarily mean that all carbon-based additives in the negative electrode material are 0-dimensional carbon-based additives, but also means that 0-dimensional carbon-based additives are the components with the majority weight percentage. When D=1, D=2 or D=3, the situation is similar.
[0032] In some optional embodiments, the negative electrode material includes: amorphous carbon and conductive carbon black; the negative electrode material satisfies: 0.001≤d50' / d50≤0.05.
[0033] In a specific embodiment, the negative electrode material includes: amorphous carbon and conductive carbon black; the dimensional matching degree W between the amorphous carbon and the conductive carbon black is 3.76, and the d50' / d50 is 0.003.
[0034] In a specific embodiment, the negative electrode material includes: amorphous carbon and conductive carbon black; the dimensional matching degree W between the amorphous carbon and the conductive carbon black is 3.50, and the d50' / d50 is 0.003.
[0035] In a specific embodiment, the negative electrode material includes: amorphous carbon and conductive carbon black; the dimensional matching degree W between the amorphous carbon and the conductive carbon black is 4.50, and the d50' / d50 is 0.003.
[0036] In some optional embodiments, the negative electrode material comprises: amorphous carbon and carbon nanotubes; the negative electrode material satisfies: 0.001≤d50' / d50≤0.12, preferably satisfies 0.001≤d50' / d50≤0.1.
[0037] In a specific embodiment, the negative electrode material includes: amorphous carbon and carbon nanotubes; the dimensional matching degree W between the amorphous carbon and the carbon nanotubes is 3.5, and the d50' / d50 is 0.003.
[0038] In a specific embodiment, the negative electrode material includes: amorphous carbon and carbon nanotubes; the dimensional matching degree W between the amorphous carbon and the carbon nanotubes is 4.16, and the d50' / d50 is 0.001.
[0039] In a specific embodiment, the negative electrode material includes: amorphous carbon and carbon nanotubes; the dimensional matching degree W between the amorphous carbon and the carbon nanotubes is 4.16, and the d50' / d50 is 0.100.
[0040] In a specific embodiment, the negative electrode material includes: amorphous carbon and carbon nanotubes; the dimensional matching degree W between the amorphous carbon and the carbon nanotubes is 4.16, and the d50' / d50 is 0.0007.
[0041] In a specific embodiment, the negative electrode material includes: amorphous carbon and carbon nanotubes; the dimensional matching degree W between the amorphous carbon and the carbon nanotubes is 4.16, and the d50' / d50 is 0.120.
[0042] In a specific embodiment, the negative electrode material includes: amorphous carbon carbon nanotubes; the dimensional matching degree W between the amorphous carbon and the carbon nanotubes is 4.50, and the d50' / d50 is 0.003.
[0043] In some optional embodiments, the negative electrode material includes: amorphous carbon and thin-layer graphene, wherein the number of layers of the thin-layer graphene is 3; and the negative electrode material satisfies: 0.001≤d50' / d50≤0.02.
[0044] In a specific embodiment, the negative electrode material includes: amorphous carbon and thin-layer graphene, wherein the number of layers of the thin-layer graphene is 3; the dimensional matching degree W between the amorphous carbon and the thin-layer graphene is 3.50, and the d50' / d50 is 0.003.
[0045] In a specific embodiment, the negative electrode material includes: amorphous carbon and thin-layer graphene, wherein the number of layers of the thin-layer graphene is 3; the dimensional matching degree W between the amorphous carbon and the thin-layer graphene is 3.66, and the d50' / d50 is 0.014.
[0046] In a specific embodiment, the negative electrode material includes: amorphous carbon and thin-layer graphene, wherein the number of layers of the thin-layer graphene is 3; the dimensional matching degree W between the amorphous carbon and the thin-layer graphene is 4.50, and the d50' / d50 is 0.003.
[0047] In some optional embodiments, the negative electrode material includes: amorphous carbon and artificial graphene; the negative electrode material satisfies: 0.001≤d50' / d50≤0.07.
[0048] In a specific embodiment, the negative electrode material includes: amorphous carbon and artificial graphene; the dimensional matching degree W between the amorphous carbon and the artificial graphene is 3.50, and the d50' / d50 is 0.003.
[0049] In a specific embodiment, the negative electrode material includes: amorphous carbon and artificial graphene; the dimensional matching degree W between the amorphous carbon and the artificial graphene is 4.26, and the d50' / d50 is 0.061.
[0050] In a specific embodiment, the negative electrode material includes: amorphous carbon and artificial graphene; the dimensional matching degree W between the amorphous carbon and the artificial graphene is 4.50, and the d50' / d50 is 0.003.
[0051] Electrochemical Devices
[0052] In the electrochemical device described in the third aspect of the present invention, it includes a negative electrode sheet, the negative electrode sheet includes a current collector layer and a negative electrode material layer located on the current collector layer, and the negative electrode material layer includes the negative electrode material as described above.
[0053] In the present invention, the electrochemical device may generally be a conventional device in the art containing the negative electrode sheet as described above, such as a secondary battery, a capacitor, and the like.
[0054] In the present invention, in the negative electrode material layer, the content of the negative electrode material may be 80.0wt%-99.9wt%, where the percentage is the weight percentage of the negative electrode material in the negative electrode material layer.
[0055] Optionally, the negative electrode material layer further includes a binder and a thickener.
[0056] There is no particular limitation on the thickener. The addition of the thickener can increase the system viscosity of the components in the negative electrode active material layer. Generally, a sodium carboxymethyl cellulose (CMC) solution can be selected.
[0057] The binder may be a binder conventionally used in the art for preparing negative electrodes. For example, the following materials may be used as the binder: one or more of SBR, PAA, CMC and PVDF.
[0058] In an optional embodiment of the present invention, the negative electrode material layer includes: amorphous carbon, a carbon-based additive, a thickener and a binder.
[0059] In a specific embodiment of the present invention, the negative electrode material layer includes: amorphous carbon, carbon-based additives, sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0060] In the embodiment of the present invention, the current collector used in the current collector layer can be a common current collector or a composite current collector according to the actual needs of the electrochemical device. The negative electrode current collector can use a material that does not cause chemical changes and has conductivity without restriction. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon or aluminum-cadmium alloy, or copper, stainless steel material or aluminum-cadmium alloy surface-treated with carbon, nickel, titanium or silver can be used. In addition, in order to enhance the adhesion of the negative electrode active material, micro-embossing can be formed on the surface of the negative electrode current collector. The negative electrode current collector can be used in various forms, such as a film, a sheet, a foil, a mesh or a porous body.
[0061] The thickness of the current collector is, for example, 16 μm.
[0062] In the present invention, the negative electrode sheet can be prepared by conventional methods in the art. For example, the following method can be used: after amorphous carbon, carbon-based additives, thickeners and binders are mixed in a certain mass ratio, a solvent is added and mixed evenly to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the current collector; and then the negative electrode sheet is prepared through processes such as drying, rolling, and cutting.
[0063] Optionally, in a specific embodiment of the present invention, the electrochemical device is a sodium ion battery, and the sodium ion battery includes the negative electrode sheet, the positive electrode sheet, the isolation membrane and the electrolyte.
[0064] In some embodiments of the present invention, a positive electrode sheet is prepared by coating a positive electrode active material including a positive electrode active material on a positive electrode current collector, and a binder, a conductive agent and a thickener may be further added as needed.
[0065] For the positive electrode current collector, materials that do not cause chemical changes and have high conductivity can be used without restriction according to the actual needs of the electrochemical device. For example, stainless steel, aluminum, nickel, titanium or calcined carbon can be generally used, or aluminum or stainless steel materials surface-treated with carbon, nickel, titanium, silver, etc. In order to enhance the adhesion of the positive electrode active material, micro-embossing can be formed on the surface of the positive electrode current collector. The positive electrode current collector can be used in various forms, such as a film, a sheet, a foil, a mesh or a porous body.
[0066] In some embodiments of the present invention, the positive electrode active material may be a sodium ion material such as a layered oxide, a Prussian blue compound or a polyanion compound. Further optionally, the general formula of the layered oxide is Na x [MFeMn]O2, M is selected from at least one of Cu, Ni, Li, Mg, Al, Zn, Ti, Zr and Sn, and x≤0.7.
[0067] In a specific embodiment of the present invention, the molecular formula of the positive electrode active material is NaNi 0.34 Fe 0.33 Mn 0.33 O2.
[0068] In some embodiments, the isolation membrane can be a polypropylene isolation membrane or a polyethylene isolation membrane.
[0069] Wherein, the thickness of the isolation film may be 9 μm.
[0070] In a preferred embodiment, the isolation membrane is a 9 μm polyethylene membrane coated on both sides with a ceramic coating with a thickness of 2 μm.
[0071] In some embodiments, the electrolyte may be an electrolyte conventionally used for batteries in the art, generally including a non-aqueous solvent, a sodium salt, and an additive.
[0072] Wherein, the non-aqueous solvent can be a conventional non-aqueous solvent in the art, preferably an ester solvent, and more preferably a carbonate solvent. The carbonate solvent can be selected from one or more of ethylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).
[0073] Among them, the additive can be selected from one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), dithiothreitol (DTD), vinylene sulfate, 1,3-propane sultone (PS), allyl sultone and 1,4-butane sultone.
[0074] The sodium salt may be a conventional sodium salt in the art, such as NaPF6.
[0075] In the present invention, the preparation method of the sodium ion battery can be a conventional preparation method in the art, which can be a battery cell obtained by winding the positive electrode sheet, the negative electrode sheet and the isolation film, and then packaging them in a packaging shell and injecting the electrolyte; or it can be a battery cell obtained by stacking the negative electrode sheet, the isolation film, the positive electrode sheet and the isolation film in this order, and then packaging them in a packaging shell and injecting the electrolyte.
[0076] Electronic devices
[0077] The electronic device described in the fourth aspect of the present invention includes the above-mentioned electrochemical device.
[0078] In the present invention, the electronic device described in the present invention can be but is not limited to mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.
[0079] On the basis of being in accordance with the common sense in the art, the above-mentioned optional conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0080] The reagents and raw materials used in the present invention are conventional reagents and raw materials, all of which are commercially available.
[0081] Examples 1-16 and Comparative Examples 1-4
[0082] Preparation of amorphous carbon
[0083] The amorphous carbon in Examples 1-16 and Comparative Examples 1-4 is hard carbon, and the preparation method thereof adopts the following steps:
[0084] The coconut shell is washed three times with a mixed solution of water and ethanol (volume ratio of 1:1), and then filtered, dried, and ground to obtain a coconut shell precursor; the coconut shell precursor is placed in a crucible, heated to 200-600°C at 1-10°C / min under a nitrogen atmosphere, and kept warm for 2-10 hours to obtain a carbon precursor; the carbon precursor is washed three times with nitric acid / hydrochloric acid / hydrofluoric acid (volume ratio of 1:1:1), and then washed with deionized water for more than 5 times, and dried to obtain an amorphous carbon precursor; the amorphous carbon precursor is heated to 1000-1500°C at 1-10°C / min under a nitrogen atmosphere, and kept warm for 2-10 hours; and then ball-milled to a desired particle size to obtain amorphous carbon, wherein the amorphous carbon obtained is hard carbon.
[0085] Amorphous carbon with different particle size distributions in Examples 1-16 and Comparative Examples 1-4 was obtained by adjusting the above process parameters.
[0086] The carbon-based additives in Examples 1-16 and Comparative Examples 1-4 are all commercially available, such as from Cabot, Yiruishi or Temeco, and the performance differences are not significant, which does not affect the purpose of the present invention.
[0087] Particle size distribution testing of amorphous carbon and carbon-based additives
[0088] The test method of d10, d50 and d90 of amorphous carbon is as follows: take 50 mg of sample and add 5 drops of 1% ethylphenyl polyethylene glycol aqueous solution, then add 20 mL of deionized water and ultrasonicate to fully disperse it, and use laser particle size analyzer to test its particle size volume distribution. The particle refractive index is 2.68, the solvent refractive index is 1.33, and the shading degree is 5%-10%. The maximum particle size of amorphous carbon particle size distribution from small to large, accounting for 10% of the volume fraction, is recorded as d10, the maximum particle size from small to large, accounting for 50% of the volume fraction, is recorded as d50, and the maximum particle size from small to large, accounting for 90% of the volume fraction, is recorded as d90.
[0089] The test method for the particle size d50' of carbon-based additives is as follows: Place the carbon-based additive particles under a transmission electron microscope for observation, select more than 100 particles in an arbitrary area, count the length of each particle in the longest direction, calculate the average value to obtain the average diameter, which is d50' (the particles counted are single particles, and agglomerated particles need to be counted as monomers).
[0090] In the negative electrode sheets of Examples 1-16 and Comparative Examples 1-4, the types, particle size distribution, dimensions of the amorphous carbon and carbon-based additives in the negative electrode material layer and the relationship between the amounts thereof are listed in Table 1.
[0091] Preparation of negative electrode
[0092] The preparation method of the negative electrode sheet adopts the following steps:
[0093] According to the dosage in Table 1, amorphous carbon, carbon-based additive, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 100: (0.1-12): 1: 2, and deionized water was added as a solvent, and the mixture was stirred to be uniform to obtain a negative electrode slurry; the negative electrode slurry was uniformly coated on a 16 μm aluminum foil current collector. After drying, rolling, cutting and other processes, the negative electrode sheets of Examples 1-16 and Comparative Examples 1-4 were prepared.
[0094] Table 1 Negative electrode material composition of Examples 1-16 and Comparative Examples 1-4
[0095]
[0096]
[0097] Effect Example 1
[0098] (1) Preparation of sodium ion batteries:
[0099] Preparation of positive electrode: layered oxide with molecular formula NaNi 0.34 Fe 0.33 Mn 0.33 The positive electrode active material of O2, conductive carbon black (Super P), carbon nanotubes (CNT), and binder polyvinylidene fluoride (PVDF) are mixed evenly according to the mass ratio of 100:2:1:3, and then N-methylpyrrolidone (NMP) is added and stirred to make it dispersed evenly to obtain the positive electrode slurry of sodium ion battery; the positive electrode slurry is evenly coated on 16μm thick aluminum foil. After drying, rolling and cutting, the positive electrode sheet is obtained.
[0100] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and propylene carbonate (PC) are uniformly mixed in a volume ratio of 1:1:1:1, and then an appropriate amount of NaPF6 is dissolved in the above mixed solution to prepare an electrolyte with a concentration of 1 mol / L.
[0101] Preparation of the diaphragm: The diaphragm is a 9 μm polyethylene diaphragm coated on both sides with a ceramic coating with a thickness of 2 μm.
[0102] Preparation of sodium ion battery: The prepared positive electrode sheet, separator, negative electrode sheet of Examples 1-16 and Comparative Examples 1-4 and electrolyte are assembled in sequence, so that the positive electrode sheet, separator, negative electrode sheet of Examples 1-16 and Comparative Examples 1-4 and separator are combined alternately, and a soft-pack battery with a capacity of 1Ah is obtained through formation.
[0103] (2) The sodium ion batteries prepared from the negative electrode materials of Examples 1-16 and Comparative Examples 1-4 were tested as follows:
[0104] Test method for 2C rate retention of sodium ion battery: At 25℃, charge to 4.0V at 0.33C rate with constant current and constant voltage (constant voltage cutoff current is 0.05C), then discharge to 1.5V at 0.33C rate with constant current and constant voltage to obtain 0.33C capacity. Charge to 4.0V at 0.33C rate with constant current and constant voltage (constant voltage cutoff current is 0.05C), then discharge to 1.5V at 2C rate with constant current and constant voltage to obtain 2C capacity. The ratio of 2C capacity to 0.33C capacity is recorded as 2C rate retention rate.
[0105] The test method for the energy density of sodium ion batteries is as follows: At a constant temperature of 25°C, charge to 4.0V at a constant current and voltage of 0.33C (the constant voltage cut-off current is 0.05C), and then discharge to 1.5V at a constant current of 0.33C to obtain 0.33C energy. Repeat the charge and discharge process 3 times, and the last 0.33C energy is recorded as the cell energy; weigh the cell mass with a balance, and the ratio of the cell energy to the cell mass is the energy density.
[0106] The results of the above tests are listed in Table 2.
[0107] Table 2 Electrochemical performance data of sodium ion batteries prepared from the negative electrode materials of Examples 1-16 and Comparative Examples 1-4
[0108]
[0109]
[0110] According to the data in Table 2, the sodium ion battery made from the amorphous carbon and negative electrode sheet of Examples 1-16 has a 2C rate retention rate of not less than 79.1% and an energy density of not less than 129.5Wh / kg, indicating that it has excellent rate performance and energy density.
[0111] When the carbon-based additive is 0-dimensional conductive carbon black, the d10, d50, d90, (d90-d10) / d50 and W of Example 10 are slightly higher than those of Example 1, and the d10, d50 and d90 of Example 11 are slightly higher than those of Example 1, but (d90-d10) / d50 and W are slightly lower than those of Example 1. Compared with the three, Example 1 has the best 2C rate retention rate and energy density.
[0112] When the carbon-based additive is a one-dimensional carbon nanotube, the d10, d90, (d90-d10) / d50 and W of Example 12 are slightly higher than those of Example 5, and d50 is slightly lower than that of Example 5; the W of Examples 6-9 is 4.16, the d10, d50, d90 and d50' / d50 of Example 7 are slightly higher than those of Example 6, the d10 and d90 of Example 8 are slightly higher than those of Example 6, and d50 and d50' / d50 are slightly lower than those of Example 6; the d50, d90 and d50' / d50 of Example 9 are all slightly higher than those of Example 6, and d10 is slightly lower than that of Example 6; among Examples 5-9 and 12, Example 7 has the best 2C rate retention and energy density.
[0113] When the carbon-based additive is a two-dimensional three-layer graphene, the carbon-based additive content, d10, d50, d90 and d50' / d50 of Example 4 are slightly lower than those of Example 2, and (d90-d10) / d50 and W are higher than those of Example 2. The carbon-based additive content, d10, d50, d90, (d90-d10) / d50, d50' / d50 and W of Example 13 are slightly lower than those of Example 2. Among Examples 2, 4 and 13, Example 2 has the best 2C rate retention and energy density.
[0114] When the carbon-based additive is three-dimensional artificial graphite, the d50, d90, (d90-d10) / d50 and W of Example 14 are slightly higher than those of Example 3, and the carbon-based additive content, d10, d50' / d50 are slightly lower than those of Example 3; the d10, d50 and d90 of Example 15 are slightly higher than those of Example 3, and the carbon-based additive content, (d90-d10) / d50, W and d50' / d50 are slightly lower than those of Example 3; among Examples 3, 14-15, Example 3 has the best 2C rate retention rate and energy density.
[0115] The carbon-based additive content of Example 16 is higher than that of Example 1. Compared with the two, Example 1 has better 2C rate retention and energy density.
[0116] Comparative Example 1 does not contain a carbon-based additive, and the 2C rate retention rate and energy density of the battery prepared therefrom are poor.
[0117] Compared with the embodiment, the W of comparative example 2 is too high, and the W of comparative example 3 is too low. The 2C rate retention rate and energy density of the batteries prepared in comparative examples 2 and 3 are lower than those in the embodiment.
[0118] The W of Comparative Example 4 is too high, and further, d50' / d50 is 0.1520. Compared with the examples, the 2C rate retention rate and energy density of the battery prepared in Comparative Example 4 are also poor.
[0119] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A negative electrode material, characterized in that: It includes amorphous carbon and a carbon-based additive; wherein the amorphous carbon contains hard carbon, and the dimensional matching degree of the amorphous carbon and the carbon-based additive is W, and the W satisfies: 3.5≤W≤4.5; wherein the W is calculated according to the following formula: W=2(d90-d10) / d50+D; Wherein, d10, d50 and d90 represent the particle size of the amorphous carbon; D represents the dimension of the carbon-based additive, and D is 0, 1, 2 or 3.
2. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies: 0.001≤d50′ / d50≤0.1, wherein d50 represents the particle size of the amorphous carbon; and d50′ represents the average particle size of the carbon-based additive.
3. The negative electrode material according to claim 1, characterized in that The amount of the carbon-based additive is 0.1wt%-10wt%, where the percentage is the weight percentage of the carbon-based additive to the amorphous carbon.
4. The negative electrode material according to claim 1, characterized in that The carbon-based additive meets any of the following conditions: a. D=0, and the carbon-based additive is selected from one or more of conductive carbon black, carbon quantum dots and fullerene; b. D=1, and the carbon-based additive is selected from one or more of carbon nanotubes, carbon fibers and carbon nanowires; c. D=2, the carbon-based additive includes thin-layer graphene, wherein the thin-layer graphene is graphene with 5 or less layers; d. D=3, the carbon-based additive is selected from one or more of artificial graphite, natural graphite, multilayer graphene and mesophase carbon microspheres, wherein the multilayer graphene is graphene with 5 or more layers.
5. The negative electrode material according to claim 1, characterized in that The negative electrode material comprises: amorphous carbon and conductive carbon black; the negative electrode material satisfies: 0.001≤d50' / d50≤0.05; Alternatively, the negative electrode material comprises: amorphous carbon and carbon nanotubes; the negative electrode material satisfies: 0.001≤d50' / d50≤0.
1.
6. The negative electrode material according to claim 1, characterized in that The negative electrode material comprises: amorphous carbon and thin-layer graphene, wherein the number of layers of the thin-layer graphene is 3; the negative electrode material satisfies: 0.001≤d50' / d50≤0.02; Alternatively, the negative electrode material includes: amorphous carbon and artificial graphene; the negative electrode material satisfies: 0.001≤d50' / d50≤0.
07.
7. An electrochemical device comprising a negative electrode sheet, characterized in that: The negative electrode sheet comprises a current collector layer and a negative electrode material layer located on the current collector layer, and the negative electrode material layer comprises the negative electrode material according to any one of claims 1 to 6.
8. The electrochemical device according to claim 7, characterized in that In the negative electrode material layer, the content of the negative electrode material is 80.0wt%-99.9wt%, where the percentage is the weight percentage of the negative electrode material in the negative electrode material layer.
9. The electrochemical device according to claim 7, characterized in that The electrochemical device is a sodium ion battery.
10. An electronic device, characterized in that: It comprises the electrochemical device as claimed in any one of claims 7 to 9.
Citation Information
Patent Citations
Preparation method of microcrystalline graphite-hard carbon composite negative electrode material
CN107437613A
Negative electrode pole piece and secondary battery
CN109286020A
High-energy-density fast-charging lithium ion battery negative electrode active material
CN112397691A
Negative plate and sodium ion battery comprising same
CN116454274A
Negative active material for rechargeable lithium battery, and rechargeable lithium battery including same
US20170117546A1